2008
DOI: 10.1021/la8022997
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Glycoacrylate-Based Polymer-Tethered Lipid Bilayers on Benzophenone-Modified Substrates

Abstract: Polymer-tethered lipid bilayers are promising models for biological membranes as they may provide a soft, lubricating environment with sufficient spacing between the substrate and bilayer for incorporating transmembrane proteins. We present such a system that uses a glycoacrylate-based telechelic lipopolymer in combination with a lipid analogue. Characterization of the mixed monolayers of lipopolymers and free lipids at the air-water interface is used to examine the molecular organization that dictates the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…number of compounds has been found suitable for this purpose, in particular polymers [17,22] and oligomers [23][24][25][26] of ethyleneoxide but also oligopeptides bearing thiol groups [27] and acrylates. [28][29][30][31][32][33][34] In a series of contributions we and others demonstrated that tailored poly(2-oxazoline) (POx) lipopolymers are a highly versatile system for the construction of PTMs. [35][36][37][38][39][40][41][42][43][44] POx-based PTMs have been successfully used to determine lateral mobility and functionality of reconstituted membrane proteins, [17,23,41,42,45] to modulate the interactions between substrate and membrane [46] but also the PTM structure.…”
Section: Introductionmentioning
confidence: 99%
“…number of compounds has been found suitable for this purpose, in particular polymers [17,22] and oligomers [23][24][25][26] of ethyleneoxide but also oligopeptides bearing thiol groups [27] and acrylates. [28][29][30][31][32][33][34] In a series of contributions we and others demonstrated that tailored poly(2-oxazoline) (POx) lipopolymers are a highly versatile system for the construction of PTMs. [35][36][37][38][39][40][41][42][43][44] POx-based PTMs have been successfully used to determine lateral mobility and functionality of reconstituted membrane proteins, [17,23,41,42,45] to modulate the interactions between substrate and membrane [46] but also the PTM structure.…”
Section: Introductionmentioning
confidence: 99%
“…First, the small distance between the bilayer and the rigid substrate may be insufficient for foreign species to penetrate through the membrane. [16] Second, electrostatic interactions between the charged lipid head groups and the surface may modify the diffusion behavior of the transmembrane molecules. [17] The Langmuir balance is a simple but powerful tool for the construction and investigation of monolayers at gas/liquid interfaces with the ability to control surface pressure and composition.…”
Section: Introductionmentioning
confidence: 99%
“…Atomic force microscopy (AFM) operated in a contact mode can merely measure the height difference between the membrane surface and the area scratched under high forces. [18] An alternative way to evaluate the structures of such multilayered systems involves techniques based on reflectivity, such as ellipsometry [19][20][21] and specular X-ray and neutron reflectivity. [22][23][24][25][26][27] Taking the basic framework of Fresnel reflectivity, one can calculate the thickness and/or refractive index of the layered structures from the two measured ellipsometric angles.…”
Section: Introductionmentioning
confidence: 99%